Regional legal consequences of the separation of the notion of registered office - Silvia CRISTEA; Camelia STOICA (Juridical Tribune, 2011)
Starting from the importance of defining the registered office with the commercial law, this study aims at analyzing the legal connotations of the business office in the fiscal law. The separations of the notions originate in the European regulations included in Law no 31/1990 regarding the commercial companies. Law no 105/1992 regarding the international private law, the Fiscal Code, and the International Conventions regarding the avoidance of double taxation. Depending on the fiscal legal status of the subject as either resident or non-resident, this study aims at finding what are the differences and the relations between the institutions called: registered office – business office.